The Effect of a Competitive Futsal Match on T Lymphocyte Surface Receptor Signaling and Functions - Cury-Boaventura, Maria F.; Gorjão, Renata; de Moura, Nivaldo R.; Santos, Vinicius C.; Bortolon, José R.; Murata, Gilson M.; Borges, Leandro da Silva; Momesso, César M.; Dermargos, Alexandre; Pithon-Curi, Tania C.; Hatanaka, Elaine (Frontiers in Physiology, 2018)
In this study, the lymphocyte activation status (surface expression of CD95, CD28, CD25, and CTLA-4), lymphocyte number, lymphocyte subpopulations, lymphocyte necrosis and/or apoptosis, and lymphocyte release of reactive oxygen species (ROS) were investigated in blood samples from 16 futsal athletes before and immediately following a competitive match. Lymphocytes were isolated from the blood samples, and the cellular parameters were assessed by flow cytometry. The futsal match induced lymphocytosis and lymphocyte apoptosis, as indicated by phosphatidylserine externalisation, CD95 expression, and DNA fragmentation. Additionally, the competitive match induced the necrotic death of lymphocytes. No alterations were observed with respect to the percentage of CD4+ and CD8+ T cells or in the T-helper/suppressor profile before and immediately after the match. Additionally, after the futsal match, the CD95 and CD28 expression levels were decreased, and the lymphocytes spontaneously released higher levels of ROS. Regardless of the origin, the situation-specific knowledge of lymphocyte behaviour obtained herein may facilitate the design of strategies to control the processes that result in infection and tissue injury and that subsequently decrease athletic performance.